Working conditions of commercial drivers: a scoping review of psychosocial work factors, health outcomes, and interventions - Mustapha Amoadu; Jacob Owusu Sarfo; Edward Wilson Ansah (BMC, 2024)
Abstract Background Psychosocial work factors significantly influence both organisational and worker health. Poor management of these factors can create precarious working conditions, risking drivers' health. This review maps evidence on the health impact of these factors and health interventions targeting the working conditions and unhealthy habits of commercial drivers. Method The search was conducted in four main databases (PubMed, Central, JSTOR and Dimensions Ai) and other sources like Google Scholar. In All, 28,039 articles were retrieved and through a rigorous screening process, 68 records were included in this scoping review. Results This review found that drivers work in precarious conditions like long driving hours, low job resources and social support, low job control, poor remuneration, workplace abuse and sexual harassment, work-family conflict, lone driving hour, irregular shift work, lack or insufficient breaks during work hours and difficult access to social protection and sanitation facilities. These precarious working conditions may expose drivers to mental health issues, cardiovascular diseases, HIV/AIDs, stroke, chronic fatigue, kidney and bladder issues and musculoskeletal pains. Most health promotion interventions target behaviour at the individual level, such as the benefits of a healthy diet and exercise, with little effort to improving working conditions. Conclusion Employers in the road transport sector need to implement health promotion interventions that focus on drivers' well-being. Additionally, improving working conditions and enforcing occupational health and safety standards in the road transport sector are essential for creating a safe and healthy workplace for all commercial drivers.